Analysis of subtle structures using different 3D survey geometries - CO2CRC Otway project case study - Ziramov, S.; Pevzner, R.; Urosevic, Milovan (2017)
Three vastly different 3D seismic surveys acquired in the Otway basin since 2000 are analyzed and compared in terms of resolution, imaging accuracy and also field methodology. The main differences between the surveys were with respect to the data density, source parameters and the unit cell design. The first survey was executed in a conventional manner using arrays on both source and receiver side. Subsequent surveys utilised single geophone/single source approach. After unified processing was applied to all three surveys, the result revealed a striking difference in resolution and fault expression between the surveys. Of particular interest was the difference between the two latest surveys that utilised single source/single receiver approach. Significant improvement in resolution provided by the latest survey is attributed to very dense spatial sampling and the unit cell designed that assumed ÄRL/ÄR ratio of 5 rather than more common ratio of 10. Consequently this survey provided very accurate images of the shallow faults which existence was not previously known. Three surveys analyzed also witness the improvements in seismic acquisition technology over the period of nearly two decades that enabled new data acquisition trends to be developed and applied.